Microstructure and mechanical properties of PM Fe-Cu-Al2O3 alloys - Celik, Ertugrul; Islak, Serkan; Kir, Durmus; Ilkilic, Cumali (Natl Inst Optoelectronics, 2013)
The purpose of this study was to investigate the effect of Cu addition on the microstructure and mechanical properties of PM Fe-Cu-Al2O3 alloys produced using hot-pressing method. Copper powder was added to iron powder at 5 wt.%, 10 wt.% and 15 wt.% rates. Production of Fe-Cu-Al2O3 alloys was carried out under pressure of 35 MPa, at 750, 800 and 850 degrees C, and for a sintering time of 4 minutes. Microstructure phase composition, relative density, hardness, and transverse rupture strength of the alloys were investigated. Phase composition and microstructure of the alloys were characterised by optical microscopy, X-ray diffraction and scanning electron microscope (SEM-EDS) techniques. The transverse rupture strength (TRS) of the samples was assessed by means of a three-point bending test. Hardness of Fe-Cu-Al2O3 alloys changed between 57 HB and 110 FIB depending on the amount of Cu and sintering temperature. Results show that the TRS of the alloys decreased together with the increase in the amount of copper, while it increased with increasing sintering temperature.
Keywords: PM; Fe-Cu-Al2O3 alloy; Sintering; Microstructure; TRS